XRD And AFM Study Of Zirconium Substituted Zn-Ni Ferrite Using Solution Combustion Method (International Journal of Engineering and Computer Science, 2017)
ZrxZn0.5-xNi0.5Fe2O4 (x=0.00, 0.05 and 0.15) has been synthesized successfully using solution combustion method with the use of high purity nitrates and fueling agent urea. XRD study of obtained sample confirms the cubic spinel structure formation. AFM reveals the surface morphology and microstructure of well dispersed Zn-Ni ferrite nanoparticles to be spherical.